Pilot epidemiological study of cleft lip and/or palate inh Kota Kinabalu, Sabah - Cheng, Chai Siew; Jimeno, SKL; Sasidaran, R; Sergius, A (Asian Journal of Medical Sciences, 2013)
Objective: To identify number of cases and the type of cleft lip and/or palate managed in government tertiary center (Queen Elizabeth Hospital) in Kota Kinabalu; and to analyze the associative factors of cleft lip and/or palate. Methods: A retrospective cross-sectional study carried out in Hospital Queen Elizabeth, Kota Kinabalu, Sabah from January 2011 to December 2012. Data from 162 new cases, which were referred for cleft lip and/or palate, were included in the study. Result: Cleft lip and palate was the most common type. While cleft lip with or without palate had higher preponderance towards male patients, secondary palate however was more common among female patients. These results were statistically significant. Conclusion: Further and larger scale study need to be carried out to identify the incidence of cleft lip and/or palate in Sabah, and its associated genetic and environmental risk factors. Early identification and intervention for cleft lip and palate need to be emphasized. DOI: http://dx.doi.org/10.3126/ajms.v4i3.8170 Asian Journal of Medical Sciences 4(2013) 86-91